Analytical Study of the Parents’ Role on the Children’s Achievement in Payaman Village, Mejobo District, Kudus Regency - Rivia Ayu Ningrum; Imaniar Purbasari; Much. Arsyad Fardani (EduBasic Journal: Jurnal Pendidikan Dasar, 2021)
This study aims to determine the classification of parents' roles on children's learning achievements in Payaman Village. Payaman was chosen as the research subject because it has students with different levels of achievement in the upper class and various economic conditions. This study's benefits are to increase the children's enthusiasm for learning and make parents more aware of their role to the fullest. The type of research used was qualitative with a descriptive approach. This research employed data collection techniques, including the stages of observation, interviews, and documentation. The data analysis utilized was descriptive qualitative. The results showed that there were five classifications of the parents’ role on children's learning achievement: providing encouragement in the form of understanding always to be optimistic, guiding children to learn in the form of accompanying children in learning, giving good examples to children by not turning on electronic equipment when the children were learning, smooth communication with children in the form of questioning difficulties faced by children, and fulfilling children's learning completeness by providing in children's school facilities in the form of tools. This study concludes that the parents’ role is vital in children's learning achievements. Therefore, parents should be able to apply the five roles of parents so that the children are active and motivated in learning to accomplish maximum achievement.